Love in a Time of Climate Change : Honoring Creation, Establishing Justice - Delgado, Sharon E. (Book collections on Project MUSE., 2017)
Love in a Time of Climate Change challenges readers to develop a loving response to climate change, which disproportionately harms the poor, threatens future generations, and damages God's creation. This book creatively adapts John Wesley's theological method by using scripture, tradition, reason, and experience to explore the themes of creation and justice in the context of the earth's changing climate. By consciously employing these four sources of authority, readers discover a unique way to reflect on planetary warming theologically and to discern a faithful response. The book's premise is that love of God and neighbor in this time of climate change requires us to honor creation and establish justice for our human family, for future generations, and for all creation. From the introduction: "As we entrust our lives to God, we are enabled to join with others in the movement for climate justice and to carry a unified message of healing, love, and solidarity as we live into God's future, offering hope in the midst of the climate crisis that 'another world is possible.' God is ever present, always with us. Love never ends."